Answer:
x² + 4x + 3
Step-by-step explanation:
to find f(g(x)), substitute x = g(x) into f(x)
f(g(x)) = f(x + 2) = (x + 2)² - 1 = x² + 4x + 4 - 1 = x² + 4x + 3
Ned must have scored an avg. of 14 points per game in his 6 games total.
Hello There
Its pretty tricky but here is your answer
<span>4833.977
Want full answer? here
</span>
<span>4833.97738
Good luck brainy
</span>
Answer:
+ 9x +18
Step-by-step explanation:
multiply the parentheses together (x × x)=x² and x×6=6x then do 3×x which will equal 3x and then multiply 3 and 6 which is 18
now combine like terms (x²+6x+3x+18)
6+3=9 so now you will have x²+9x+18